Identifikasi Keterampilan Berbicara Yang Diajarkan Guru Kelas VI Sekolah Dasar - Mufidatul Khusna; Debby Rahmawati; Befa Damai Revolusi; Shofiatul Karimah; Gesti Kinasih Hardhini; Conny Dian Sumadi (Jurnal Bintang Pendidikan Indonesia, 2023)
This study aims to find or identify speaking skills taught by grade VI elementary school teachers. This research is a qualitative type of research using descriptive methods. Data collection techniques used in the form of interviews and documentation studies. The subject of this study was a grade VI teacher at UPTD SD Negeri Banyuajuh 2. The results of interviews that have been conducted show that there are four speaking skills taught, which include interviews, role plays or drama, speeches, and group discussions. The four speaking skills are integrated in Indonesian language learning materials in grade VI elementary school.